Overview of california studies on noise reduction for asphalt and concrete surfaces - Harvey, John T.; Wu, Rongzong; Guada, Irwin M.; Lu, Qing; Öngel, Aybike; Rezaei, Arash; Kohler, Erwin R. (CRC Press/Balkema, 2017)
California researchers have evaluated the noise reducing performance and durability of standard mixes, including open-graded and rubberized open-graded mixes, rubberized gap graded mixes and dense graded mixes over more than 6 years of monitoring and ages of more than 15 years. Empirical modeling was used to identify the most promising mixes under different conditions of traffic and climate. The results were also used to develop new mix types to further increase noise and durability performance using smaller maximum stone sizes, while continuing use of rubberized binders. A new approach for designing open graded mixes for noise in the laboratory was also developed. For concrete pavement, a similar study evaluated existing texture types, as well as new texture types using grind and groove technology. The concrete sections have been evaluated for noise and skid performance for several years. Recommendations are presented for next steps in the development and implementation of these results. © 2019 Elsevier B.V., All rights reserved.
10th International Conference on the Bearing Capacity of Roads, Railways and Airfields, BCRRA 2017 -- Athens -- 220519
Keywords: Bearing capacity; Concretes; Durability; Railroads; Concrete surface; Dense graded mixes; Durability performance; Empirical model; Gap graded mix; New approaches; Noise reducing; Standard mixes; Noise abatement